Analysis of Automatic Voltage Regulator (AVR) Performance Based on Commissioning Load Acceptance and Load Rejection Data at 28 MW Capacity Steam Power Plant - Winarto, Agung Tri; Sunardi, Sunardi; Sutikno, Tole (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
As the load changes, the voltage produced by the generator will always change due to the fluctuating load. The output voltage must be kept constant within the desired value to ensure the supply of generator output power in order to meet the needs of the load, then a device called AVR (Automatic Voltage Regulator) is needed. AVR aims to regulate the amount of excitation current supplied to the generator and the amount of excitation current is directly proportional to the amount of voltage produced by the generator. This study aims to analyze the performance of AVR in maintaining the stability of voltage and generator output power at 28 MW Steam Power Plant. Monitoring the performance of the AVR installed on the generator is carried out during commissioning and testing. The test results and analysis after the generator is installed AVR can be seen that the output voltage is in stability with a variation value between 5% of the nominal output voltage value of 11 KV, which shows the success of installing AVR to stabilize the output voltage remains constant and can meet the needs of the load.